2021
DOI: 10.3389/fphar.2021.676020
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of Potentially Inappropriate Medication in Older Inpatients of an Internal Medicine Ward: Concordance and Overlap Among the EU(7)-PIM List and Beers and STOPP Criteria

Abstract: Background: Age-related comorbidities prone older adults to polypharmacy and to an increased risk of potentially inappropriate medication (PIM) use. This work aims to analyze the concordance and overlap among the EU(7)-PIM list, 2019 Beers criteria, and Screening Tool of Older Person’s Prescriptions (STOPP) version 2 criteria and also to analyze the prevalence of PIM.Methods: A retrospective cohort study was conducted on older inpatients of an internal medicine ward. Demographic, clinical, and pharmacological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 55 publications
5
27
0
Order By: Relevance
“…The AGS/Beers criteria judge each medicine as a PIM based not only on the medication profile of a patient but also on the pathologies of the patients, as well as the laboratory results ( O'Mahony et al, 2015 ). In order to apply the STOPP criteria, it is imperative to know the entire medication history, clinical information of the patient, and laboratory ( O'Mahony et al, 2015 ; O'Mahony, 2020 ; Perpétuo et al, 2021 ). Based on the 2019 AGS/Beers criteria, our study found that the prevalence of PIM use among older Chinese cancer patients was 32.65%, which was lower than the prevalence of 80.4% reported by a study on Korean cancer patients according to the 2019 AGS/Beers criteria ( Suh et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The AGS/Beers criteria judge each medicine as a PIM based not only on the medication profile of a patient but also on the pathologies of the patients, as well as the laboratory results ( O'Mahony et al, 2015 ). In order to apply the STOPP criteria, it is imperative to know the entire medication history, clinical information of the patient, and laboratory ( O'Mahony et al, 2015 ; O'Mahony, 2020 ; Perpétuo et al, 2021 ). Based on the 2019 AGS/Beers criteria, our study found that the prevalence of PIM use among older Chinese cancer patients was 32.65%, which was lower than the prevalence of 80.4% reported by a study on Korean cancer patients according to the 2019 AGS/Beers criteria ( Suh et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The search strategy was limited to the three main health research databases and articles written in English, Portuguese, and Spanish. The included studies were heterogeneous in practice settings, population, size of the samples, and PIM definition that can be variable depending on the screening tool used, which can influence PIM number detected ( Thomas and Thomas, 2019 ; Perpétuo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is a five-step, patient-centered systematic approach ( Figure 2 ) used for evaluating and discontinuing medications in patients where potential harms exceed potential benefits in relation to individual existing functioning capability, care goals, preferences, values and life expectancy. Hence, this process suspends medication, changes medication, and decreases medication dosages for obtaining the best clinical outcomes [ 34 ]. This is because deprescribing approaches are patient-specific and focused and follow interventions with appreciable variability in medications used and patient characteristics [ 35 ].…”
Section: Deprescribing Approachesmentioning
confidence: 99%